2004
DOI: 10.1149/1.1760993
|View full text |Cite
|
Sign up to set email alerts
|

Stagnation Flow Reactor Investigation of Tin Oxide CVD from Monobutyltin Trichloride

Abstract: Tin oxide (SnO 2 ) chemical vapor deposition from monobutyltin trichloride ͑MBTC͒ was performed in a stagnation flow reactor at reduced pressures ͑15-100 Torr͒ and temperatures of 573-923 K. Growth from MBTC/O 2 mixtures exhibits multiple activation energies, decreasing from 18.8 Ϯ 1.1 kcal mol Ϫ1 at temperatures р673 K to 11.4 Ϯ 1.1 kcal mol Ϫ1 at temperatures Ͼ673 K, indicating a change from one growth mechanism to another. Heterogeneous chemistry governs growth from these precursors at р673 K and most likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Such a high deposition rate as well as the experimental observation of the wave shape deposition profile (will be discussed later) imply that the deposition process of SnO 2 from MBTC might be mainly limited by the flow behavior as well as mass transport in the coating zone and that the effect of reaction kinetics is less important. This assumption is further substantiated by the experimental measurement of tin oxide deposition rate at different temperatures [7,8]. As a result, the CFD modeling of on-line APCVD coating on glass can be done with reasonable accuracy without a highly developed reaction mechanism and kinetic data.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Such a high deposition rate as well as the experimental observation of the wave shape deposition profile (will be discussed later) imply that the deposition process of SnO 2 from MBTC might be mainly limited by the flow behavior as well as mass transport in the coating zone and that the effect of reaction kinetics is less important. This assumption is further substantiated by the experimental measurement of tin oxide deposition rate at different temperatures [7,8]. As a result, the CFD modeling of on-line APCVD coating on glass can be done with reasonable accuracy without a highly developed reaction mechanism and kinetic data.…”
Section: Introductionmentioning
confidence: 81%
“…The numerical simulation based on CFD is able to provide quantitative information of flow behavior and species transport, but typically relies to a large extent on the thermodynamic data, reaction mechanism, and transport properties. Monobutyltin trichloride (or MBTC) used for SnO 2 deposition in the glass industry, which is of interest in the current work, has very limited data reported in the literature [6][7][8][9][10][11]. While it is experimentally shown that the reaction of MBTC with oxygen is accelerated in the presence of water, the function of water in the decomposition and/or oxidation of MBTC, is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reactions of tin tetrachloride with water and oxygen are relatively fast, Eley-Rideal mechanisms are not very likely since the loss of entropy and the minimal chance that molecules collide in the exact configuration needed for a reaction will give an extremely low pre-exponential factor, and so reaction rate. 9 The last group is represented by Chae et al 10,11 who interpreted their results also in terms of an Eley-Ridealtype of mechanism during his study on monobutyl tin chloride (MBTC, n-C 4 H 9 SnCl 3 ) with oxygen. However, for the deposition of MBTC with oxygen and water, the authors proposed that first a gas-phase complex of MBTC with water must be formed before the complex can adsorb at the surface and react with oxygen in an Eley-Rideal-type of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The oxide coating maintains the high pristine strength of glass [1,2]. Tin dioxide is currently used industrially for its high transparency to visible light and high hardness and is deposited from organometallic precursors such as tin tetrachloride (SnCl 4 ) [3,4] or monobutyltintrichloride (n-C 4 H 9 SnCl 3 ) [5][6][7][8][9]. The second one, called "cold-end coating", consists in a spray deposition of an organic water-based formulation (polyethylene, waxes, oleic acid …) at bottle temperatures between 80 °C and 160 °C [10,11].…”
Section: Introductionmentioning
confidence: 99%